PERUBAHAN SOSIAL ULAON ADAT MANGOMPOI JABU (MEMASUKI RUMAH BARU) PADA MASYARAKAT BATAK TOBA DI DESA GONTING GAROGA, KECAMATAN GAROGA, KABUPATEN TAPANULI UTARA - Tambunan, Mida Rotua; Sinambela, Maringan; Simbolon, Rusmauli; Firmando, Harisan Boni; Simbolon, Elvri Teresia (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This research is entitled Social Changes in the Ulaon Custom of Mangompoi Jabu in the Toba Batak Community in Gonting Garoga Village, Garoga District, North Tapanuli Regency, namely the tradition of entering a new house which has been passed down from generation to generation and is still passed down from ancestors to this day, but not many people carry out this custom anymore so The meaning in this series of customs cannot be seen and people are no longer very enthusiastic in understanding the meaning of the custom of entering a house or mangompoi jabu. This research aims to determine the meaning and social changes of the Mangompoi Jabu custom. This research uses qualitative research using a qualitative approach method through observation and in-depth interviews. The results of the research show that the traditional mangompoi tradition is carried out by the Toba Batak people to interpret this custom as not only a tradition but also in the form of saying thanks and asking for prayers to their lover so that they will always be blessed by the house they have just moved into and is also a motivation for them. old where through this custom a child is no longer at liberty to sell the house. Apart from that, there is a change that has occurred where the change is in the form of the type of implementation of the Mangmpoi Jabu custom, where nowadays the Mangompoi Jabu custom has often been replaced with the Mangopi-api i custom or just a partangiagan or just praying together for various reasons, one of which is economic. Apart from that, for Batak people, the family is lacking, when the house has been carried out by the mangompoi jabu custom, the house can no longer be sold and some parents or children cannot guarantee this because there are many things they guard